Stanisław Bednarski SJ and prof. Stanisław Kot: pupil and master - Stanisław Cieślak SJ (Studia Historiae Scientiarum)
On September 15th 1922, a young Jesuit, Father S. Bednarski, enrolled at the Jagiellonian University, Department of Philosophy, Faculty of Humanities, with specialization in modern history, history of culture and history of art. One of his college professors was a well-known historian, Prof. Stanisław Kot.